Organic waste processing and its application to potato plants through hydroponic techniques - Irmawanty Irmawanty; Dian Safitri; Wira Yustika Rukman; Haerul Syam (JPBIO (Jurnal Pendidikan Biologi), 2021)
The Kalimbu market is one of the traditional markets in South Sulawesi with a very high buying and selling activity. The organic waste that is mostly generated from the activities at the Kalimbu Market is leftover vegetables and fruit. Vegetable and fruit waste provides a big advantage if it is managed properly, which is converted into liquid organic fertilizer through a fermentation process. The liquid organic fertilizers produced can help farmers overcome the high price of synthetic fertilizers and save the earth from pollution. The method used to determine the effect of types of organic waste (vegetable waste and fruit waste) on the physical and chemical quality of solid and liquid organic fertilizers used a randomized block design. Whereas the application of solid and liquid organic fertilizers to the production and nutritional content of potato plants used a treatment consisting of P0: basic fertilizer + without liquid organic fertilizer and P1: basic fertilizer + liquid organic fertilizer. The results of research on the manufacture of liquid organic fertilizer from Kalimbu market waste with vegetable and fruit samples also showed that the two samples required different storage times for composting. Plants treated with liquid organic fertilizer from the Kalimbu market waste have better stem growth, leaf number, and stem number.Keywords: Waste, organic, fermentation, hydroponic